2020
DOI: 10.1097/mpg.0000000000002529
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Intestinal Failure Is Independently Associated With Impaired Cognitive Development Later in Childhood

Abstract: Objective: The impact of pediatric intestinal failure (IF) on neurodevelopment beyond infancy has not been systematically studied. Our aim was to evaluate cognitive and motor impairment and to identify risk factors for adverse outcomes among children with IF. Methods: We conducted a cross-sectional single-center study at the Helsinki University Children's Hospital. Patients with IF with >60 days of parental nutrition (PN) dependency aged between 3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…[2][3][4] Clinical and experimental data showing that lipid reduction or lipid modification regimens in PN solutions may reverse PNAC have been met by concerns about compromised neurodevelopment in the face of inadequate lipid provision. [5][6][7][8] In addition to the role of PN lipid emulsions, [9][10][11][12] intestinal inflammation 13 or resection are essential factors in promoting PNAC, involving dysbiosis, altered intestinal barrier function with increased absorption of bacterial products, including lipopolysaccharides (LPSs), that stimulate cytokine production by liver macrophages and downregulation of hepatocyte bile and sterol transporters.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Clinical and experimental data showing that lipid reduction or lipid modification regimens in PN solutions may reverse PNAC have been met by concerns about compromised neurodevelopment in the face of inadequate lipid provision. [5][6][7][8] In addition to the role of PN lipid emulsions, [9][10][11][12] intestinal inflammation 13 or resection are essential factors in promoting PNAC, involving dysbiosis, altered intestinal barrier function with increased absorption of bacterial products, including lipopolysaccharides (LPSs), that stimulate cytokine production by liver macrophages and downregulation of hepatocyte bile and sterol transporters.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven studies were of retrospective design (19,23–32), 19 of prospective design (20–22,33–48). Sample size across studies ranged from 10 to 449 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Eleven studies were of retrospective design (19,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32), 19 of prospective design (20)(21)(22)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48). Sample size across studies ranged from 10 to 449 patients.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Skallerup et al (11) found a significantly increased risk of sarcopenia in adults with IF and Mangus et al (12) reported severe sarcopenia in children with IF-related end-stage organ disease. Children with IF can also present with delays in motor development from infancy through school age (13)(14)(15)(16). Lower levels of motor competence can be associated with lower levels of physical activity (PA) and decreased muscle strength and endurance (17).…”
mentioning
confidence: 99%